(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Le possibili implicazioni religiose di una “stretta di mano” - 2. Il caso sottoposto all’esame dei giudici svedesi - 3. La pronunzia del 15 agosto 2018, n. 51, del Tribunale del lavoro svedese e la questione della ricorrenza di una “pratica religiosa” meritevole di tutela - 4. (segue) La verifica dei presupposti di una “discriminazione indiretta” - 5. L’esperienza d’Oltreoceano - 6. Identità religiosa e (dis)uguaglianza di genere - 7. La diversa incidenza, nella fattispecie esaminata, del divieto di discriminazione per motivi religiosi e del principio della parità di genere - 8. Conclusioni: la libertà religiosa della lavoratrice e i margini lasciati alle scelte di politica aziendale della società. Dealing with the contentious points of the integration (about “forbidden” greetings and principle of non-discrimination) ABSTRACT: Some Islamic believers adhere to a rule of behavior coming from a particular reading of the traditions concerning the life of Muhammad, so they do not shake hands with people of the other sex outside their own restricted family circle. The present paper analyzes the potential impact of such a choice, if it is carried out in the work context and it infringes specific internal company rules, which require employees to not discriminate against customers on the basis of sex. The Author, in accordance with a recent decision of the Swedish Labor Court, affirms that the limitation of the freedom of the worker can be considered a case of indirect discrimination for religious reasons. However, demanding that the woman abstains from shaking hands with persons of her own sex, as suggested by the Court, is not required by the principle of gender equality, and is not coherent with the very personal nature of the act, according to the Author.